Branchiomeric Muscle Development Requires Proper Retinoic Acid Signaling - Wang, Qi; Xu, Lin; Miura, Jiro; Saha, Mithun Kumar; Uemura, Yume; Sandell, Lisa L.; Trainor, Paul A.; Yamashiro, Takashi; Kurosaka, Hiroshi (Frontiers in Cell and Developmental Biology, 2021)
The first and second branchiomeric (branchial arch) muscles are craniofacial muscles that derive from branchial arch mesoderm. In mammals, this set of muscles is indispensable for jaw movement and facial expression. Defects during embryonic development that result in congenital partial absence of these muscles can have significant impact on patients’ quality of life. However, the detailed molecular and cellular mechanisms that regulate branchiomeric muscle development remains poorly understood. Herein we investigated the role of retinoic acid (RA) signaling in developing branchiomeric muscles using mice as a model. We administered all-trans RA (25 mg/kg body weight) to Institute of Cancer Research (ICR) pregnant mice by gastric intubation from E8.5 to E10.5. In their embryos at E13.5, we found that muscles derived from the first branchial arch (temporalis, masseter) and second branchial arch (frontalis, orbicularis oculi) were severely affected or undetectable, while other craniofacial muscles were hypoplastic. We detected elevated cell death in the branchial arch mesoderm cells in RA-treated embryos, suggesting that excessive RA signaling reduces the survival of precursor cells of branchiomeric muscles, resulting in the development of hypoplastic craniofacial muscles. In order to uncover the signaling pathway(s) underlying this etiology, we focused on Pitx2, Tbx1, and MyoD1, which are critical for cranial muscle development. Noticeably reduced expression of all these genes was detected in the first and second branchial arch of RA-treated embryos. Moreover, elevated RA signaling resulted in a reduction in Dlx5 and Dlx6 expression in cranial neural crest cells (CNCCs), which disturbed their interactions with branchiomeric mesoderm cells. Altogether, we discovered that embryonic craniofacial muscle defects caused by excessive RA signaling were associated with the downregulation of Pitx2, Tbx1, MyoD1, and Dlx5/6, and reduced survival of cranial myogenic precursor cells.